Appetitive Aggression in Women: Comparing Male and Female War Combatants - Meyer-Parlapanis, Danie; Weierstall, Roland; Nandi, Corina; Bambonyé, Manassé; Elbert, Thomas; Crombach, Anselm (Frontiers in Psychology, 2016)
Appetitive aggression refers to positive feelings being associated with the perpetration of violent behavior and has been shown to provide resilience against the development of PTSD in combatants returning from the battlefield. Until this point, appetitive aggression has been primarily researched in males. This study investigates appetitive aggression in females. Female and male combatants and civilians from Burundi were assessed for levels of appetitive aggression. In contrast to non-combatants, no sex difference in appetitive aggression could be detected for combatants. Furthermore, each of the female and male combatant groups displayed substantially higher levels of appetitive aggression than each of the male and female civilian control groups. This study demonstrates that in violent contexts, such as armed conflict, in which individuals perpetrate numerous aggressive acts against others, the likelihood for an experience of appetitive aggression increases- regardless of whether the individuals are male or female.